ACTIVE JUDGES IN ADVERSARIAL COMMON LAW AND THEIR RELEVANCE TO INDONESIA’S HYBRID CRIMINAL PROCEDURE - Setyawan , Vincentius Patria; Wisnubroto , Aloysius (PT. Jurnal Center Indonesia Publisher, 2025)
This research examines the relevance of adopting the concept of active judges within adversarial common law traditions to Indonesia’s hybrid criminal procedure. The primary objective is to explore whether the active judge model can strengthen Indonesia’s criminal justice reform without undermining its civil law foundation. This study employs a normative juridical method with a comparative approach, analyzing doctrinal sources, statutory law, and scholarly debates from both civil law and common law perspectives. The findings suggest that while the adversarial system traditionally restricts judges to a passive role, the notion of an active judge has emerged to prevent procedural abuses and ensure substantive justice. For Indonesia, integrating aspects of the active judge model may contribute to enhancing transparency, protecting defendants’ rights, and harmonizing procedural justice with societal expectations. Nevertheless, challenges remain, particularly concerning judicial independence, consistency of application, and potential conflicts with established inquisitorial practices. This study concludes that the adoption of active judge principles must be carefully contextualized, reinforcing Indonesia’s hybrid system rather than replacing its legal traditions.